Pengaruh Motivasi, Disiplin Kerja Dan Kemampuan Kerja Terhadap Kinerja Asn Pada Dinas Kepemudaan, Olahraga Dan Pariwisata Kabupaten Jombang Di Masa Pandemi Covid-19 - Prapto Wardoyo; Edy Swasono (Universitas Islam Kadiri, 2022)
This study aims to analyze whether: (1) there is an influence of motivation, work discipline and work ability on the performance of ASN employees at Dinas Kepemudaan, Olahraga Dan Pariwisata of Jombang Regency, This study used is a quantitative approach by using survey method. The respondents are 30 employee. The results revealed that: simultaneously Motivation, Work discipline and Work ability have a positive affect on the performance of ASN employees at Dinas Kepemudaan, Olahraga Dan Pariwisata of Jombang Regency. (2) while Partially Motivation does not have no an effect on the performance of ASN employees. (3) Partially, both of Work Discipline and work ability habe a positive effect on the performance of ASN employees of Dinas Kepemudaan, Olahraga Dan Pariwisata of Jombang Regency. It is recommended that the head of Dinas to increase the employee’s motivation in working.